TEXNOLOGIYA FANI O‘QITUVCHILARI TAYYORLASHDA “XALQ HUNARMANDCHILIGI VA BADIIY LOYIHALASH” FANIDAN TA’LIM MAZMUNI VA METODLARINI TAKOMILLASHTIRISH - Tojiyev, J.K. (SCIENCE and SOCIETY, 2023)
The article deals with the problems in the educational process in the subject "Folk crafts and decoration" in the direction of the bachelor’s degree "Technological education", and also provides recommendations for improving the educational process. In particular, the ways of improving the content of teaching students in folk crafts and practical arts, ways of developing their theoretical knowledge and practical skills, as well as an analysis of the teaching methods in use are described.